An analysis on strategy evolution of research & development in cooperative innovation network of new energy vehicle within policy transition period. (October 2022) - Han, Jing; Guo, Ju-E; Cai, Xun; Lv, Cheng; Lev, Benjamin
Highlights: A novel framework for using optimal research & development (R&D) investment to derive the innovation motivation of the new energy vehicle (NEV) industry is constructed. An industry game model is established to explore dynamic influence of policy transition imposed on the R&D strategy evolution of the innovation entities. Considering the difference of R&D preference, seven decision-making scenarios of innovative entities are proposed. The rate of subsidy reduction should be regulated, and dual-credit policy should be promoted steadily and actively. The cooperative innovation network exists an optimal connectivity that maximizes the proportion of the suppliers' R&D strategy. Abstract: Insufficient motivation and investment in research and development (R&D) will hamper further developing of the new energy vehicle (NEV) industry. In response to this dilemma, the Chinese government has successively issued the subsidy and dual-credit policies. This study aims at exploring the influence mechanism of the policy transition imposed on the R&D strategy evolution in NEV cooperative innovation network, thus constructing a two-level game model accordingly. Specifically, the inversion method is used a posteriori in the first level to address suppliers' optimal R&D investment. Then, the optimal R&D investment and patent data are used in the second level to construct the network game model, thereby analyzing the influences of the policy transition and of network characteristics on suppliers' R&D strategy evolution. Simulation results suggest that within the subsidy reduction stage, suppliers prefer to choose independent R&D strategy. To summarize, the implementation of the dual-credit policy can reduce the heavy dependence of suppliers' technology R&D upon subsidies while increasing the proportion of suppliers choosing cooperative R&D. In the NEV cooperative innovation network, the evolution of suppliers' R&D strategy can be effectively promoted via not only the controlling over the optimal network clustering coefficient but also the influence of the key nodes within.